Small airway dysfunction predicts excess ventilation and dynamic hyperinflation during exercise in patients with COPD. (November 2020) - Manco, Alessandra; Pisi, Roberta; Aiello, Marina; Tzani, Panagiota; Frizzelli, Annalisa; Fantin, Alberto; Alfieri, Veronica; Bertorelli, Giuseppina; Chetta, Alfredo
Abstract: Introduction: Small airway dysfunction (SAD) is a pathophysiological characteristic of chronic obstructive pulmonary disease (COPD). Excess ventilation and dynamic hyperinflation (DH) are two main pathophysiological traits and limiting factors of COPD patients while exercising. We aimed to ascertain whether or not SAD, assessed by the multiple breath nitrogen washout (MBNW), may predict exercise ventilatory inefficiency and DH. Methods: Fifty stable COPD patients were prospectively studied and underwent MBNW and incremental cardio-pulmonary exercise test (CPET). Indices of conductive (Scond ) and acinar (Sacin ) ventilation heterogeneity as well as minute ventilation/CO2 production (VE /VCO2 ) linear relationship and the change in inspiratory capacity (IC) were analyzed. Results: Sacin was significantly and directly related to VE /VCO2 slope and inversely related to IC change and to peak O2 uptake ( p < 0.01 for all correlations). No significant correlation was found between Scond and CPET parameters. The regression equation generated by stepwise multiple regression analysis for the VE /VCO2 slope and IC change, as dependent variables, included only Sacin, as independent variable. This model accounted for 31% and 36% of the total variance for the VE /VCO2 slope and IC change, respectively. Conclusion: Our study shows the value of the SAD as determinant of the excess ventilation and DH during exercise in patients with stable COPD. Highlights: The main pathophysiological traits of COPD patients while exercising are the excess ventilation and dynamic hyperinflation. In COPD patients, Sacin, a marker of small airway dysfunction, can predict excess ventilation and dynamic hyperinflation. Small airways dysfunction crucially impacts on functional status of COPD patients.